Optimization of solid fermentation conditions of organic fertilizer from fish and tobacco wastes and its effects on crop production and soil quality - Aimin Liu; Juan Yu; Hongli Feng; Kailu Zhang; Cunlong Lu; Xiancan Zhu (Emirates Journal of Food and Agriculture)
Microbial fermentation fertilizer from agricultural organic wastes represents a novel, environmentally friendly, and safe type of bio-organic fertilizer. However, the development and application of solid fermentation using fish by-products and plant waste straw is still rare. In this study, the fermentation substrate and conditions were optimized by single factor test and orthogonal test using fish waste and tobacco waste as raw materials, and its effects on plant growth and soil quality were investigated. The results showed that the addition of 0.5% sodium chloride and 1% ammonium nitrate to the fish waste fermentation substrate, along with a ratio of Bacillus subtilis: Rhodotorula rubrosaensis: Rhizobium oryzae at 2:1:3, a 30% addition of tobacco waste, an inoculation amount of 4×1010 CFU/g, and a fermentation temperature of 34 °C, resulted in the best fermentation conditions. Pot experiment demonstrated that application of fish waste fermentation fertilizer significantly increased average fresh weight, dry weight, and chlorophyll content of Brassica rapa by 131.6, 60.0, and 18.5% respectively, and Capsicum annuum by 74.3, 46.7, and 195.4% respectively, compared with no fertilizer treatment. The activity of urease, invertase and catalase in soils with fish waste fermentation fertilizer application were significantly higher than no fertilizer application. Moreover, the relative abundances of nitrogen-fixing and denitrifying bacteria were improved after application of fish waste fermentation fertilizer. Fish waste fermentation fertilizer significantly affected the functional genes related to carbohydrate metabolism and increased the utilization rate of organic fertilizer. This study provides a theoretical basis for the future fermentation processes of fish waste and its application in crop production.